Evaluation the efficacy of immunological response in sheep vaccinated with Brucella melitensis strain Rev 1: W. S. AL- Khafaji and M. I. AL-Farwachi - AL- Khafaji, W. S. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study aimed to identify the efficacy of Brucella melitensis vaccine strain Rev 1 in induction of antibodies by different doses and routes of administration; also to obtain the specificity of the serological tests, the study included 28 ewes divided into four equal groups . the animals of first and second groups vaccinated subcutaneously with 2×109 and 2×107 colony forming units (CFU) respectively while the animals of third and fourth groups vaccinated conjunctively with 2×109 and 2×107 CFU respectively . The sera were collected at zero time, 2, 4, 8, 16, 20, 24 and 28 weeks of the experiment and the antibodies response were evaluated using classical tests ( Rose Bengal, serum agglutination and 2-mercaptoethanol tests ) compared with competitive ELISA test , and brucellin test was used to detect the cellular response . The results showed that antibody titers were higher and remained for longer period in subcutaneously vaccinated groups in both doses compared with those vaccinated conjunctively and the 2-mercaptoethanol test show the best specificity in all vaccinated groups; also the subcutaneously vaccinated groups recorded significant increase in skin thickness in brucellin test after 12 week post vaccination .There was a significant increase in neutrophils activity for reduction of nitrobluetetrazolium stain in all groups between 2nd and 8th post vaccination